The Learning Paradigm College – John Tagg - Gallagher, Eugene V. (Teaching theology and religion, 2006)
Books reviewed: The Learning Paradigm College. By John Tagg. Boston, Mass.: Anker Publishing Co., 2003. xviii & 379 pages. ISBN 1-8829-8258-4. USD39.95 (Cloth).